Intelligent auxiliary system oriented to academic field - LIU YAN; ZHANG QINGGUO (2024)
The invention discloses an intelligent auxiliary system oriented to the academic field, relates to the technical field of academic research, and aims to guide a user to select a research direction and a paper topic and recommend a paper outline through cue words so as to help the user to clear writing thinking and logic and improve writing efficiency and quality. The system comprises a paper writing module which is used for responding to an intelligent auxiliary request and obtaining a plurality of preset prompt words; obtaining a research theme input by a user, generating a first research direction by using the research theme, and generating a first writing question and answer statement by using the first research direction; in response to the first selection instruction, generating a first paper question by using the research subject and the target research direction, and generating a second writing question and answer statement by using the first paper question; in response to the second selection instruct